Increased levels of antibodies to cytokeratin 18 in patients with rheumatoid arthritis and ischaemic heart disease. Issue 4 (12th March 2004) - Mattey, D L; Dawes, P T; Nixon, N B; Goh, L; Banks, M J; Kitas, G D
Abstract : Objective: To determine whether raised levels of antibodies to CK18 in patients with RA are associated with ischaemic heart disease (IHD). Methods: IgA, IgG, and IgM antibodies to CK18 were measured by enzyme linked immunosorbent assay (ELISA) in patients with RA with (n = 34) or without (n = 28) IHD. The relationship between CK18 antibody levels and markers of inflammatory and/or cardiovascular disease was examined. Results: Initial analysis showed that IgG antibody levels to CK18 were higher in patients with RA with IHD than in those without (50.1 v 34.5 AU, p = 0.047), although significance was lost after correction for multiple comparisons. Further analysis showed a significant difference (p = 0.015) between patients with IHD and a positive family history, and patients without IHD and a negative family history (53.7 v 29.0 AU, Kruskal-Wallis multiple comparison Z value test). There was also a significant trend of increasing 10 year cardiovascular risk with increasing CK18 IgG antibody levels (p = 0.01). No association was found between CK18 antibody levels and conventional markers of inflammation or cardiovascular disease, but an association was found between levels of CK18 IgG and IgG antibodies to cytomegalovirus (CMV) (Spearman's r s = 0.379, pcorr = 0.04). No evidence for cross reactivity of CK18 antibodies with CMV antigens was found. Conclusion: Levels of IgG antibodies to CK18 are raised in patients with RA with IHD, particularly if they also have a positive family history. This may reflect damage to CK18 containing cells in the cardiac vasculature and/or in atherosclerotic plaques, and may be a useful additional marker for the identification of patients with, or likely to develop, IHD.